Pattern of Injuries in Fatal Road Traffic Accidental Cases (An Autopsy-Based Study) (AYUSHDHARA, 2025)
Aim: The aim of this study was to analyze the patterns of injuries in road traffic accidents (RTAs) through autopsy-based examinations, focusing on the demographics of victims, types of injuries sustained. Material and Methods: This observational survey study was conducted at the mortuary of the District Hospital, Nashik, over a one-year period from September 2015 to August 2016. The study included 385 victims of RTAs whose deaths occurred within the Nashik district. Data was collected from post-mortem examinations, inquest reports, and hospital records. The patterns of injuries were evaluated, and statistical analysis was performed using the Chi-square test with SPSS version 21.0, considering a p-value of less than 0.05 as statistically significant. Results: The majority of RTA victims were males (82.60%) aged between 20-29 years (33%). Conclusion: The findings highlight the high mortality and severe injuries sustained in RTAs, particularly in middle-aged males. Some factors like lack of traffic laws, traffic mix, drunken and rash driving, poor conditions of the road and head injuries are key contributors to fatalities, underscoring the need for enhanced road safety measures and timely medical intervention.